The Correlation Between Level of Knowledge and Attitude of Cataract Patients to Perform Cataract Surgery - Fitriani, Dian Ayu; Musafirah, Sitti; Hamzah, Arisa Putri Ardiyan (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Cataracts fill the second priority eye disease in the world, it shows that cataract is still an issue that must be resolved. Knowledge, attitudes, and behavior of Indonesian citizens on eye health is still a concern that cause poorer vision impairment. Rate of cataract cases in this study is a bit high. Purpose. To find out the correlation of knowledge levels and attitudes of cataract patients to actions in performing cataract surgery at Konawe Hospital. Research design used was observational analytics with a cross-sectional approach and accidental sampling methods. Result shows that most of the respondents have a good level of knowledge (51.4%), as well as the attitude variable was good (66.4%). Processing data by chi-square test shows analysis test p-value 0.001, it means there is a correlation between the level of knowledge to action in performing surgery. The same results are also shown in the attitude variable with p value 0.000. Therefore, level of knowledge and attitude is an important basis for patients to have, before making a decision to perform cataract surgery. This study has a substantial impact to increase rate of cataract surgery in Konawe’s Hospital.